Peningkatan Kompetensi Guru dalam Manajemen Referensi Artikel Ilmiah Melalui Pelatihan Aplikasi Mendeley: Enhancing Teachers' Competence in Managing Scientific Article References through Mendeley Application Training - Hary - Murcahyanto (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
Education in the modern era has evolved beyond mere content delivery, aiming to develop students' potential holistically. Middle school teachers in East Lombok not only serve as instructors but also as primary drivers in students' academic growth. Quality scientific writing is essential in developing students' analytical skills. However, there is still a gap in teachers' understanding of modern tools like Mendeley Reference Manager, which can support this process. Mendeley helps organize and reference sources efficiently and facilitates collaboration. This activity aims to enhance teachers' understanding of using Mendeley through training. The training was conducted over three days, from May 20 to May 23, 2020, in the Microteaching Room at Hamzanwadi University Selong. The training methods included lectures, discussions, and hands-on practice. Results showed a significant increase in teachers' understanding and skills. Active participation was demonstrated by 85% of participants who were able to use basic Mendeley features, while 75% successfully created automatic bibliographies. Additionally, 90% of participants stated that this training increased their writing efficiency. Evaluation also revealed that several participants produced quality scientific papers ready for publication in national journals. This training proved that using modern tools like Mendeley can enhance teachers' scientific writing quality, support professional development, and have a positive impact on education